SIFAT PENGOLAHAN DAN SIFAT FISIK PULP SEMBILAN JENIS KAYU DARI INDONESIA BAGIAN TIMUR - Setyani B; Lestari Lestari; Yoswita Yoswita (Pusat Penelitian dan Pengembangan Hasil Hutan, 2003)
This paper dealt with chemical processing and physical properties of wood for pulp of nine woods. The analyses consisted of pulp screen yield, alkali consumption, permanganate number, breaking length, and tearing factor. This analysis is very important in determining the suitability of wood species as raw material for pulp paper production.Results of chemical pulping process indicated that pulp screen yield in a range of 32.70 - 47.71 %, alkali consumption 12.20 - 15.50 %, permanganate number 9.75 - 20.70, breaking length value 2.60 - 4.40 km, bursting factor 27.51 - 51.27, tearing factor 74 - 132, and folding endurance 4.5 - 59.5 df. The results revealed that all wood species were suitable for pulp and paper production. Chemical processing of these wood species produced high pulp screen yield, low alkali consumption, pulp easily bleached pulp and good physical pulp properties. Two of the species, Horsfieldia sylvetris Warb and Calophyllum inophyllum L. resulted in the best quality of pulp.